2015
DOI: 10.1377/hlthaff.2014.1352
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Closures Had No Measurable Impact On Local Hospitalization Rates Or Mortality Rates, 2003–11

Abstract: The Affordable Care Act (ACA) set in motion payment changes that could put pressure on hospital finances and lead some hospitals to close. Understanding the impact of closures on patient care and outcomes is critically important. We identified 195 hospital closures in the United States between 2003 and 2011. We found no significant difference between the change in annual mortality rates for patients living in hospital service areas (HSAs) that experienced one or more closures and the change in rates in matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 21 publications
(23 reference statements)
3
58
0
Order By: Relevance
“…), hospital closures (Joynt et al. ), workplace wellness programs (Caloyeras et al. ), and quality reporting (Hollenbeak et al.…”
Section: Basics Of Difference‐in‐differencesmentioning
confidence: 99%
“…), hospital closures (Joynt et al. ), workplace wellness programs (Caloyeras et al. ), and quality reporting (Hollenbeak et al.…”
Section: Basics Of Difference‐in‐differencesmentioning
confidence: 99%
“…5 Moreover, hospitals that close tend to have lower occupancy rates and poorer financial performance, and recent hospital closures have not been associated with changes in local hospitalization rates or mortality. 6 Going forward, continued efforts to slow health care spending may continue to encourage the adoption of alternatives to hospital admission.…”
Section: Why We Should Not Be Worriedmentioning
confidence: 99%
“…Current literature documenting hospital 5 6 and ED closures 7–10 has produced controversial findings; some studies have shown associations with higher mortality due to deteriorating access, 7 while others have shown no association with poorer outcomes. 6 Several studies have specifically examined closures of trauma centres, 11 12 but to our knowledge, few have discussed the population effects on outcomes as a result of trauma centre closures. 13 …”
Section: Introductionmentioning
confidence: 99%